A mid-Cretaceous dinosaur track assemblage from the Hengshan Formation in central Zhejiang, China. (3rd July 2021) - Xing, Lida; Lockley, Martin G.; Klein, Hendrik; Chou, Chunyong; Wang, Donghao; Persons, W. Scott
ABSTRACT: The Cretaceous Hengshan Formation at the Baxian tracksite, central Zhejiang has yielded more than 20 sauropod tracks with a considerable size range (pes length ranging from 22.7–83.7 cm). The assemblage consists of a more complete trackway of a large animal, a less complete trackway of a large animal with a similar orientation and, a small manus-pes set indicating a smaller trackmaker. Thus, it is a small ichnoassociation with tracks indicating different-sized trackmakers that moved in different directions. From a global perspective the assemblage is important, because it is another data point indicating the presence of different size-classes and mixed associations with very small and large sauropods, probably representing juvenile and adult individuals. These tracks are the first reported from the mid-Cretaceous of this region, being therefore slightly younger than those already known from Early Cretaceous sites, which are also attributed to sauropods.